Provocatio gegen das Urteil der duumviri perduellionis - Kuznetsova, Natalia (Hyperboreus, 2018)
The paper considers the duumviri perduellionis, a court which has long been a matter of debate. It is attested only three times: the legendary trial of Horatius during the reign of Tullus Hostilius (Liv. I, 26, 5–14; Fest. p. 390 L.; Cic. Mil. 7; Val. Max. VIII, 1, abs. 1); one version of M. Manlius Capitolinus’ death (Liv. VI, 20); and the trial of Rabirius in 63 BC for his part in quelling the Revolt of Saturninus, well-attested but inconsistently described by the sources (Cic. Rab. perd.; cf. In Pis. 4; Suet. Caes. 12; Dio Cass. XXXVII, 25, 4 – 28, 4). The purpose of this article is to answer the question of reliability of the sources pointing at the possibility to appeal to the people against the verdict of the duumviri (Suet. Caes. 12; Dio Cass. XXXVII, 25, 4 – 28, 4; Liv. I, 26, 5–14): it is the only instance of provocatio against the court verdict, not against an attempt to impose corporal punishment, a high ﬁne or capital punishment out of court. The main argument against the possibility of provocatio is Cic. Rab. perd. 12, with a number of scholars regarding it as an indication that Rabirius could not appeal against the verdict of the duumviri in the court. The paper proves that Cicero’s testimony, in fact, does not contradict the statements of Dio Cassius and Suetonius that Rabirius did appeal to the people; besides, some considerations on the reconstruction of the Rabirius trial are brought forward.